Essays on Financial Innovation, Credit Constraints, and Welfare - Janíčko, Martin, 1983- (2012)
The submitted thesis is composed of three different articles dealing with issues of financial innovation, credit constraints, and their impact on welfare. The first article treats the contemporary theoretical grasp of the interaction between the financial and real economies, focusing primarily on the role of modern financial innovation in the business cycle. For this purpose, a framework promoted by the Regulation School and Post Keynesians is frequently employed, whilst some other unorthodox streams and mainstream economics are partially discussed as well. All of them aspire -- either per se or under the pressure of the contemporary economic agenda -- to clarify the evolution of financial innovation and credit in the recent era. It is generally found that certain consensus across the schools of economic thought exists, but some of them have done a better job in predicting the consequences of the financial innovation for real economic activity than others. Further, two dynamic macroeconomic models are developed in order to, inter alia, identify the possible effects of extended credit availability presented in the former article on the example of the housing market, and simulate the effects of housing price changes on general welfare. Clearly, this part of the thesis exhibits the indirect consequences of financial innovation as, once again, being rather ambiguous: after having partially unleashed the unprecedented credit granting in the economy, impacting interest rates and loan-to-value ratios, with a subsequent impact on housing prices, it has also influenced credit constrained and unconstrained households in a different manner. Based on an analysis of the situation using partial and general equilibrium analytical frameworks, two somewhat different conclusions are drawn up with respect to the occurrence of various shocks in the models.